Design and application of a loop-mediated isothermal amplification for detection of molluscum contagiosum virus - Almasi, Mohammad Amin; Esmaili, Rozhin (Journal of Pakistan Association of Dermatologists, 2020)
Objective Molluscum contagiosum virus (MCV) is a poxvirus that causes localized papules in healthy persons. A loop-mediated isothermal amplification (LAMP) assay was developed and compared to polymerase chain reaction (PCR) assay for detection of MCV. Â Methods The p43K protein gene of virus is basically used for designing the primers. These assays were employed to examine the lesion samples taken from 50 patients, who were aged between 1 and 60 years and diagnosed with clinical MCV lesions in different parts of their bodies. Â Results 44 MCV-positive patients (88%), children aged between 1 and 10 years were a higher percentage. The results show LAMP is an advantageous method because it is highly sensitive (1000-fold), quite cheap, user-friendly, and safe; in addition, it is performed quickly by visual detection using hydroxynaphthol blue (HNB) Dye in a water bath. Â Conclusion LAMP technique can be simply and reliably applied with basic instruments through visual inspection in laboratory studies. Â